EFEKTIVITAS E-LKPD DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Nisrina Nur Azizah; Decky Avrilianda; Muh. Sholeh; Edi Kurniawan; Amin Yusuf; Tri Joko Raharjo; Indriana Eko Armaidi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine comprehensively the effectiveness of Liveworksheet-based electronic student worksheets (E-LKPD) in enhancing students' critical thinking skills in elementary science education. The research employed a Systematic Literature Review (SLR) method with a descriptive qualitative approach, following the PRISMA framework, which includes identification, screening, eligibility, and inclusion stages. Data were collected through a systematic search of scholarly articles in major academic databases, namely Google Scholar, focusing on publications from 2022 to 2025. A total of 18 articles that met the inclusion criteria were selected and analyzed using thematic and comparative synthesis techniques. The findings indicate that Liveworksheet-based E-LKPD is effective in improving students' critical thinking skills, particularly in the areas of analysis, evaluation, and problem-solving. In addition, the integration of interactive features such as multimedia elements, automated quizzes, and immediate feedback has been shown to enhance students' learning engagement. The study also reveals that increased student engagement encourages more active participation in higher-order thinking processes, while success in critical thinking tasks contributes to strengthening students' intrinsic drive to learn. Therefore, Liveworksheet-based E-LKPD can be considered an innovative and effective digital instructional tool to support elementary science learning. The implications of this study highlight the importance of HOTS-oriented instructional design and the integration of digital technology to improve the quality of 21st-century education.